Conception rates of beef heifers treated with GnRH analog at the time of estrus or at the time of artificial insemination - L.R. Corah; W.E. Beal; M.F. Spire; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1989)
Injecting a GnRH-analog at the time of estrus or at insemination did not generally improve conception rates in heifers inseminated following a synchronized estrus. However, within some herds. a significant positive response was noted.
Keywords: Cattlemen' s Day; 1989; Kansas Agricultural Experiment Station contribution; no. 89-567-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 567; Beef; Conception rates; GnRH; Estrus; Artificial insemination